The AP-1 factor JUNB correlates with poor survival of patients with esophageal adenocarcinoma - Schleußner, Nikolai; Knipper, Karl; Leugner, Ella; Goddemeier, Christian; Yasar, Uraz; Wirsik, Naita M.; Jung, Jin-On; Fuchs, Hans F.; Schiffmann, Lars M.; Quaas, Alexander; Bruns, Christiane; Schmidt, Thomas (Scientific reports, 2025)
Malignant cells have in contrast to non-transformed cells de-regulated transcriptional networks. The activator protein-1 (AP-1) transcription factor complex is expressed in many cancer entities including adenocarcinomas and has been correlated to de-regulated transcription and tumor-promoting mechanisms. Despite complex treatment approaches, esophageal cancer is still associated with poor overall survival. There is an urgent need for better patient stratification to increase the outcome of the multimodal treatment. This study investigated the expression of two AP-1 factors, cJUN and JUNB, and their role in 735 patients with esophageal cancer undergoing surgery. We performed immunohistochemical stainings for cJUN and JUNB and correlated the expression to the clinical outcome. Patients with a high JUNB expression level correlate to a reduced overall survival (OS) compared to patients with a low expression. Furthermore, in the multivariate analysis high JUNB expression was shown to be an independent risk factor for reduced patient survival. In addition, subgroup analysis demonstrated a significantly reduced OS for high JUNB expression in the subgroup of patients with neoadjuvant treatment. Strikingly, tumors co-expressing cJUN and JUNB were associated with poorer overall survival compared to those expressing only one or neither of the transcriptions factors. Our study suggests JUN expression as a novel biomarker to stratify patients, especially in the subgroup of neoadjuvant treated patients. Our findings have translational implications as targeting JUN might complement current available multimodal treatment approaches.